Interleukin-1 beta (IL-1β) and interleukin-6 (IL-6) as proinflammatory cytokines in traumatic brain injury (TBI) of rat (Sprague-Dawley) : A study of propofol administration - Riyadh Firdaus; Franciscus Dhyana Giri Suyatna; Aida Rosita Tantri; Yetty Ramli; Ekowati Handharyani; Arni Diana Fitri (Journal of Global Pharma Technology, 2020)
The increase in the prevalence of traumatic brain injury (TBI) followed by increased morbidity and mortality challenges anesthetists to perform the treatment patients with TBI. Menwhile, interleukin-1 beta (IL-1β) and interleukin-6 (IL-6) are the first pro-inflammatory markers expressed after secondary injury occurs. In addition, propofol (2,6-disopropylphenol) is a short-acting intravenous agent that reported to play role in inflammatory process. This study aims to determine the effects of propofol administration on the neuroinflammatory pathway. Thirty adult female Sprague Dawley rats were randomly assigned as TBI rats (T), rats that received propofol infusion (P), or TBI rats that received propofol infusion (TP). The rat model of TBI was developed using the Marmarou Weight Drop method. Clinical assessment was performed using the Neurobehavioral Severity Score-Revised (NSS-R). Brain tissues were taken 24 h after TBI and the levels of interleukin-1 (IL-1) and interleukin-6 (IL-6) mRNA expression levels were examined using qRT-PCR, while the concentration were examined using ELISA and immunohistochemistry. On clinical examination, a decrease in the median value of NSS-R in the TP group was found from 30th minute to 120th minute. 24 hours after the occurrence of TBI, there was a decrease in both the TP and T groups. However, the NSS-R values in the TP group were lower than those in the T group. The expression of IL-1β was found in the nuclei and cytosol, while IL-6 was found in the axons and cytosol. The expression and concentration of IL-1β and IL-6 were the highest in the TP group, followed by the P and then the T group. Propofol can improve neurological function in rats with TBI, probably through the mechanism involves neuroinflammatory pathways, particularly IL-1β and IL-6.